Globalization of Trade and Transportation between the ASEAN + 3 Countries and the European Union - Ho Thi Thu Hoa; Heda Hansenová (Romanian Journal of European Affairs, 2025)
The paper discusses the globalization process of trade and transportation between the ASEAN + 3 countries (ASEAN plus three – APT) and the EU (the European Union). An East Asian 10+3 (ASEAN plus three) cooperative framework joined by ASEAN, China, Japan and South Korea, is proceeding towards institutional direction which will play a very important role in the regional and international economic development. The paper will intensively not only focus on recent trade boom; and the necessity of transportation in order to meet objective requirements of increasing trade relations between the ASEAN + 3 and the EU but also forecast new potentials in relations of transportation and trade of the ASEAN + 3 with EU candidate member countries.